Strategi Pemasaran pada Sistem Layanan Kesehatan - Purwowiyoto, Sidhi Laksono; Ananda Vilda, Cattleya; Indri Priyobodo, Dionisius; Raisa Cicilia, Ivana (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2022)
Health marketing is interdisciplinary because it uses certain concepts, methods, and techniques for classical and social marketing. The specialty of health marketing is that there are services and markets but no money equivalent. Healthcare marketing differs mainly by the nature of the demand for health services. The beneficiary may not be the target of a marketing campaign, and the physician decides what, where, when, and how much to provide for a particular service. To understand the impact of marketing strategies on healthcare quality, it is essential to understand today's medical consumers who prefer to seek medical information online. They also have many health services, healthcare providers, and reviews from patients who contact providers.